Extraction, synthesis and characterization of nickel (II) and cobalt (II) caprate complexes - Hanane Rehali; Djamel Barkat (Journal of Applied Engineering Science and Technology, 2017)
Liquid‐liquid extraction is one of the most useful technique for selective and recovery ofmetal ions aqueous solutions, applied in purification processes in numerous chemical industries. Inthis work the liquid‐liquid extraction of nickel (II) and Cobalt (II) from aqueous solution by capricacid(HL) in chloroform at 25±0.05°C has been studied. The nickel and cobalt in capric acidmonomeric complexes, having formula of the type [M(HL)2L 2] (M :Co(II) and Ni(II). The complexeshave been characterized with the help of elemental analysis, the apparatus used is a lasergranulometer Malvern Mastersizer Type 2000/3000, this device can measure the particle sizes,conductance measurements, electronic UV‐Visible suggest that the octahedral . Fourier transforminfrared confirm the presence of bidentate carboxylate in the complexes. The thermal behavior ofcomplexes was studied by thermogravimetry (DTG), differential thermal analysis (DTA).The finaldecomposition products namely NiO and Co3O 4.